Introibo Ad Altare Dei—Visual Displaying and Liturgical Ornamentation of Christian Altars in the Late Medieval Illustrations of the Roman Rite - Ángel Pazos-López (Religions)
This study offers an in-depth exploration of the visual representation of Roman Rite liturgical altars in medieval images from the 13th to the 15th centuries, presenting a fresh perspective on the altar as a central and complex element of medieval liturgical furnishings. It examines key iconographic themes, such as the introit Ad te levavi animam meam and masses celebrated by saints, often depicting divine interventions during the Eucharist. Additionally, the research investigates the role of performative visual elements, such as curtains, which contributed to the depiction of sacred space within altar scenes. These visual devices help convey the altar as a space imbued with spiritual significance. Drawing on a wide range of contemporary visual and documentary sources, the study traces the continuity and variation in the altar’s iconography, offering a nuanced understanding of its role in medieval Christian worship. By examining how artists employed visual symbolism to emphasize the sanctity of the altar, this research sheds new light on the ways medieval altars were imagined and represented in the broader context of medieval art.